Functional programming in Scala video edition - Chiusano, Paul; Bjarnason, Rúnar (Manning Publications, 2014)
"Functional Programming in Scala is a serious tutorial for programmers looking to learn FP and apply it to the everyday business of coding. This Video Editions book guides readers from basic techniques to advanced topics in a logical, concise, and clear progression. In it, you'll find concrete examples that open up the world of functional programming. Functional programming (FP) is a style of software development emphasizing functions that don't depend on program state. Functional code is easier to test and reuse, simpler to parallelize, and less prone to bugs than other code. Scala is an emerging JVM language that offers strong support for FP. Its familiar syntax and transparent interoperability with Java make Scala a great place to start learning FP."--Resource description page